Matricellular protein tenascin C: Implications in glioma progression, gliomagenesis, and treatment - Fu, Zaixiang; Zhu, Ganggui; Luo, Chao; Chen, Zihang; Dou, Zhangqi; Chen, Yike; Zhong, Chen; Su, Sheng; Liu, Fuyi (Frontiers in Oncology, 2022)
Matricellular proteins are nonstructural extracellular matrix components that are expressed at low levels in normal adult tissues and are upregulated during development or under pathological conditions. Tenascin C (TNC), a matricellular protein, is a hexameric and multimodular glycoprotein with different molecular forms that is produced by alternative splicing and post-translational modifications. Malignant gliomas are the most common and aggressive primary brain cancer of the central nervous system. Despite continued advances in multimodal therapy, the prognosis of gliomas remains poor. The main reasons for such poor outcomes are the heterogeneity and adaptability caused by the tumor microenvironment and glioma stem cells. It has been shown that TNC is present in the glioma microenvironment and glioma stem cell niches, and that it promotes malignant properties, such as neovascularization, proliferation, invasiveness, and immunomodulation. TNC is abundantly expressed in neural stem cell niches and plays a role in neurogenesis. Notably, there is increasing evidence showing that neural stem cells in the subventricular zone may be the cells of origin of gliomas. Here, we review the evidence regarding the role of TNC in glioma progression, propose a potential association between TNC and gliomagenesis, and summarize its clinical applications. Collectively, TNC is an appealing focus for advancing our understanding of gliomas.